Commentary: Using experts by experience to enhance transitional age youth mental health services – a commentary on Adu et al. (2022). Issue 4 (17th September 2022) - Wakefield, Emma; Wakefield, Toni
Abstract : Background: In their article, 'System Transformation to Enhance Transitional Age Youth Mental Health – A Scoping Review', Joseph Adu et al. consider how, over the last 15 years, youth mental health and the transitional age from adolescents to young adulthood has received increasing attention, with 1 in 5 living with mental illness reported as being under 25. Their research on the transition to adult mental health services identifies a need for innovative, evidence‐based approaches to TAY mental health care, in response to the emerging and persistent challenges experienced globally in this area of practice. In responding to this review, the authors support the findings that when youth actively participate in service design, they experience improvements in their own mental health and are able to contribute to the evolution of evidence‐based mental health promotion and care. Examples from personal experience and research reiterate the importance of youth voice through all levels of system design. Conclusions: The benefits of co‐production are evident, both in this review and from personal experience, recognising that mental health issues have a major impact on individuals, families, and communities. The use of this approach in developing and improving youth mental health transition services is beneficial for all involved.